Indigenous naming practices in the Western Mediterranean: the case of Iberian - Moncunill Martí, Noemí (Alexandru Ioan Cuza University of Iași, 2017)
The Iberian language is directly attested by ca. 2,250 inscriptions spanning the period from the 5th century BC to the 1st century AD, distributed between Eastern Andalusia and Languedoc. Although it must be considered a non-deciphered language, a large number of personal names have been identified in Iberian texts. The document that enabled the understanding of the basic structure of Iberian names is a Latin inscription from Italy (the Ascoli Bronze) recording the grant of Roman citizenship to Iberians who had fought for Rome during the Social War (90-88 BC). The study of this document paved the way for the identification of Iberian names in texts written in local languages, on the one hand, and in Latin and Greek epigraphic and literary sources on the other. This paper provides a state-of-the-art overview of research on Iberian onomastics, by synthesising the main recent achievements along with the remaining lines of research; it also investigates our understanding of the grammatical and syntactic structure of Iberian names, and analyses the evolution of Iberian naming patterns under Roman domination, by taking into account both Iberian and Latin documents.